Pre-micro RNA signatures delineate stages of endothelial cell transformation in Kaposi sarcoma. - Andrea J O'Hara; Pauline Chugh; Ling Wang; Eduardo M Netto; Estrella Luz; William J Harrington; Bruce J Dezube; Blossom Damania; Dirk P Dittmer (PLoS Pathogens)
MicroRNAs (miRNA) have emerged as key regulators of cell lineage differentiation and cancer. We used precursor miRNA profiling by a novel real-time QPCR method (i) to define progressive stages of endothelial cell transformation cumulating in Kaposi sarcoma (KS) and (ii) to identify specific miRNAs that serve as biomarkers for tumor progression. We were able to compare primary patient biopsies to well-established culture and mouse tumor models. Loss of mir-221 and gain of mir-15 expression demarked the transition from merely immortalized to fully tumorigenic endothelial cells. Mir-140 and Kaposi sarcoma-associated herpesvirus viral miRNAs increased linearly with the degree of transformation. Mir-24 emerged as a biomarker specific for KS.